Simulating destructive and constructive morphodynamic processes in steep beaches - Kombiadou, Katerina (2021)
Short-term beach morphodynamics are typically modelled solely through storm-induced erosion, disregarding post-storm recovery. Yet, the full cycle of beach profile response is critical to simulating and understanding morphodynamics over longer temporal scales. The XBeach model is calibrated using topographic profiles from a reflective beach (Faro Beach, in S. Portugal) during and after the incidence of a fierce storm (Emma) that impacted the area in early 2018. Recovery in all three profiles showed rapid steepening of the beachface and significant recovery of eroded volumes (68–92%) within 45 days after the storm, while berm heights reached 4.5–5 m. Two calibration parameters were used (facua and bermslope), considering two sets of values, one for erosive (Hm0 ≥ 3 m) and one for accretive (Hm0 < 3 m) conditions. A correction of the runup height underestimation by the model in surfbeat mode was necessary to reproduce the measured berm elevation and morphology during recovery. Simulated profiles effectively capture storm erosion, but also berm growth and gradual recovery of the profiles, showing good skill in all three profiles and recovery phases. These experiments will be the basis to formulate event-scale simulations using schematized wave forcing that will allow to calibrate the model for longer-term changes.